The neural signature of prolonged grief: A systematic review of alterations in functional connectivity - Luana Lopes de Castro Melo; Maria Cecília César Soares e Silva; Renata Drumond Peixoto Coura; Lúcio Aparecido Moreira; Miriam Nogueira Barbosa (International Health Sciences Review, 2026)
Grief is a universal experience, marked by intense emotional, cognitive, and physiological reactions to the loss of someone significant. This systematic review, conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020), aimed to investigate and synthesize the scientific evidence regarding alterations in functional brain connectivity and the neural signature associated with prolonged grief, seeking to understand the neurobiological correlates that differentiate adaptive grief from pathological grief. Studies published between 2005 and 2025 on the neurobiological bases of grief were analyzed using the Nature, Neurology Journals, and PubMed databases, resulting in six eligible articles. The findings indicate that grief involves alterations in regions such as the prefrontal cortex, amygdala, anterior cingulate cortex, and nucleus accumbens, which are related to emotional regulation, affective memory, and attachment. Prolonged grief presents distinct patterns of brain connectivity, persistent rumination, and difficulty modulating emotional responses, distinguishing it from adaptive grief. These findings reinforce the importance of careful diagnosis to avoid inappropriate medicalization and highlight the need for multidisciplinary approaches in the management of bereaved individuals.